Lasing Characteristics of CH3NH3PbCl3 Single‐Crystal Microcavities under Multiphoton Excitation. Issue 3 (28th December 2017) - Yang, Decheng; Xie, Chao; Xu, Xuhui; You, Peng; Yan, Feng; Yu, Siu Fung
Abstract: Photoluminescence of CH3 NH3 PbCl3 single crystals under multiphoton excitation is studied. The emission intensity and wavelength, which are related to the phase of the single crystals, are found to be dependent on the operating temperature and pressure. High optical gain (>110 cm −1 @ ≈395 nm) and high absorption coefficient (≈9 × 10 −10 cm 9 GW −5 @ 2400 nm) can also be obtained from the single crystals. With suitable design of the resonant optical amplification, lasing emission at ≈395 nm is demonstrated from the single‐crystal microcavities under 2400 nm excitation. Hence, it is verified that CH3 NH3 PbCl3 single crystals can offer new opportunities for novel nonlinear photonics applications. Abstract : The photoluminescence of CH3 NH3 PbCl3 microcrystals under single‐ and multiphoton excitation is studied. The emission intensity and wavelength are found to be dependent on the phase of the crystal and can be controlled by temperature and pressure. The microcrystal is a natural vertical cavity and can support lasing action in orthorhombic phase under multiphoton excitation.